Transitioning to Second-line Antiretroviral Therapy Among Adolescents in Copperbelt Province, Zambia: Predictors of Treatment Switching and Adherence to Second-line Regimens. Issue 8 (August 2017) - Stalter, Randy M.; Katayamoyo, Patrick; Packer, Catherine; Banda, Harry; Chen, Pai-Lien; Mwansa, Jonathan K.; McCarraher, Donna R.; Denison, Julie A.
Abstract : Background: Adolescents living with HIV (ALHIV) experience less favorable antiretroviral therapy (ART) outcomes than other age groups. First-line treatment failure complicates ART management as second-line regimens can be costlier and have greater pill burdens. Understanding predictors of switching ART regimens and adherence among adolescents on second-line ART may help to prevent poor treatment outcomes. Methods: A quantitative survey was administered to 309 ALHIV attending 3 ART clinics in the Copperbelt Province, Zambia. Medical chart data, including pharmacy refill data, were abstracted. Associations between being on second-line ART and sociodemographic, psychosocial and ART adherence characteristics were tested. Cox proportional hazards models were used to estimate the effect of baseline ART variables on time to switching. Results: Ten percent of participants were on second-line regimens. Compared with ALHIV on first-line ART, adolescents on second-line regimens were older ( P = 0.02), out of school due to completion of secondary studies ( P = 0.04) and on ART longer ( P = 0.03). Adolescents on second-line regimens were more likely to report missing ≥48 consecutive hours of drugs in the last 3 months ( P = 0.01). Multivariable analysis showed that adolescents who initiated ART with efavirenz-based regimens were more likely to switch to second-line than those put on nevirapine-based regimens (hazard ratio = 2.6; 95% confidence interval: 1.1–6.4). Conclusions: Greater support is needed for ALHIV who are on second-line regimens. Interventions for older adolescents that bridge the gap between school years and young adulthood would be helpful. More research is needed on why ALHIV who start on efavirenz-based regimens are more likely to switch within this population.